Benefit Type and Care Source in Relation to Mammography Screening and Breast Cancer Stage at Diagnosis Among DoD Beneficiaries. Issue 3 (1st March 2017) - Manjelievskaia, Janna; Brown, Derek; Shao, Stephanie; Hofmann, Keith; Shriver, Craig D.; Zhu, Kangmin
ABSTRACT: Background: Type of insurance and out-of-pocket costs influence the use of medical care. Specifically, type of insurance can impact an individual's likelihood of receiving a screening mammogram. Additionally, variation in tumor stage at diagnosis exists for patients with different types of insurance. It is not clear whether different benefit types and care sources differ in breast cancer care and outcomes among Department of Defense (DoD) beneficiaries. Methods: The objective of this study was to examine differences in screening mammography and tumor stage at diagnosis between different benefit types (TRICARE Prime vs. non-Prime) and among different care sources (direct care, purchased care, and both) in the DoD Military Health System. Study subjects were women 40 to 64 years of age, diagnosed with malignant breast cancer between 2003 and 2007. Multivariable logistic regression analyses were conducted to assess differences by benefit type and care source in receipt of screening mammography before diagnosis and tumor stage at diagnosis. Findings: A total of 2, 668 women were included in this study. Patients with Prime were more likely to receive a screening mammography and have an earlier tumor stage than those with non-Prime. Women with direct care were more likely to have an earlier tumor stage but less likely to receive a screening mammogram than those with purchased care. Discussion: In an equal access health care system, the use of mammography screening and tumor stage at diagnosis may differ by benefit type and care source among DoD beneficiaries. To our knowledge, this was the first study to assess mammography screening and tumor stage differences by benefit type and care source in the Military Health System. Although underlying reasons for the differences are not clear, they may be related to out-of-pocket costs, distance from medical treatment facilities, and frequency of doctor visits for other medical problems. Further research is needed to assess these differences and related factors among DoD beneficiaries.